Dynamics of Caputo Fractional Order SEIRV Epidemic Model with Optimal Control and Stability Analysis - Mahata, Animesh; Paul, Subrata; Mukherjee, Supriya; Das, Meghadri; Roy, Banamali (International journal of applied and computational mathematics, 2022)
In mid-March 2020, the World Health Organization declared COVID-19, a worldwide public health emergency. This paper presents a study of an SEIRV epidemic model with optimal control in the context of the Caputo fractional derivative of order 0 < ν ≤ 1 . The stability analysis of the model is performed. We also present an optimum control scheme for an SEIRV model. The real time data for India COVID-19 cases have been used to determine the parameters of the fractional order SEIRV model. The Adam-Bashforth-Moulton predictor–corrector method is implemented to solve the SEIRV model numerically. For analyzing COVID-19 transmission dynamics, the fractional order of the SEIRV model is found to be better than the integral order. Graphical demonstration and numerical simulations are presented using MATLAB (2018a) software.